INDICATIONS OF WINDOW DRESSING ON COMMERCIAL BANKS IN INDONESIA - Muchlis Dr (Indonesia Banking School, 2015)
More than often, banks are ranked based on their total assets. The bigger its assets the higher its position in the rank. To maintain its position in a higher rank, a bank may take extra efforts, to maintain its total assets high, whether by increasing its performance or manipulating their financial statement like window dressing. The higher its position in the rank the more likely a bank to perform temporary banking activities at the year end to increase its assets. The examples of the such activities are increasing temporarily customer deposits in the year end. Those temporary activities in are tending toward a window dressing.This paper examines the possibilities of window dressing activities at the year end conducted by high ranked banks by temporarily pushed their assets up through extra efforts in gathering temporary customer deposits at the year end. If those window dressing activities really exist, researchers expect that data will show temporary increase in assets, customer deposits and also cost of funds of high ranked banks in Indonesia. Researcher uses the monthly data and started from January 2006 untill December 2011.This research shows an evidence that bank total assets increase significantly at the year-end and the increase is temporary. Further, the increase in total assets appears to be funded with purchased demand deposit, savings, and time deposits. This research also shows that larger banks are more likely than smaller banks to exhibit window dressing.Keywords: banks, window dressing, asset.